2016
DOI: 10.1016/j.pec.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

PETS-D (parents education through simulation-diabetes): Parents’ qualitative results

Abstract: Objective Parents who have a child newly diagnosed with type 1 diabetes (T1D) must quickly learn daily diabetes self-management. An RCT was conducted using human patient simulation (HPS) to enhance parents learning diabetes self-management with children with new-onset T1D. The purpose of this study was to describe parents’ perspectives of using HPS to augment diabetes education. Methods A qualitative descriptive design was used with open-ended in-depth interviews of parents (n=49) post-intervention. Qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…11 The value of the innovative teaching methodologies used in this study was viewed positively by the CDEs and parents alike. 23 Both vignettes and HPS-enhanced education had positive reactions from both CDEs and parents (note: parents were not asked about vignettes alone, only in conjunction with HPS) 23 and showed modest beneficial effects in quantitative outcomes. 14 This is not surprising given the effectiveness of both vignettes and HPS when used to teach health professionals and health professional students [6][7][8][9]16,17 and the effectiveness of using vignettes in adult diabetes education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 The value of the innovative teaching methodologies used in this study was viewed positively by the CDEs and parents alike. 23 Both vignettes and HPS-enhanced education had positive reactions from both CDEs and parents (note: parents were not asked about vignettes alone, only in conjunction with HPS) 23 and showed modest beneficial effects in quantitative outcomes. 14 This is not surprising given the effectiveness of both vignettes and HPS when used to teach health professionals and health professional students [6][7][8][9]16,17 and the effectiveness of using vignettes in adult diabetes education.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 There was strong consensus among parents and CDEs that HPS is very beneficial for visual learners. 23 Parents in the PETS-D study who were interviewed about their experience using HPS with vignettes to learn DSM skills stated that they appreciated having visual, hands-on simulation learning experiences because it helped alleviate parents' fears of hurting their child. They recommended that anyone who interacts with a child with T1DM be taught with this technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility of practicing skills in the simulator, before it was necessary to develop them in their children in an emergency situation, reduced the level of parents' anxiety significantly. 25 Also regarding the use of simulators to train patients, it was demonstrated that the simulation has assisted patients and caregivers in the development of skills for the care of children on mechanical ventilation in the home environment, 26 for the performance of intermittent urinary catheterization, 27 among others.…”
Section: Introductionmentioning
confidence: 99%